Outcomes of proximal humeral chondroblastoma treated with intralesional curettage, electrocauterization of the cavity and bone grafting: A retrospective study - Jingjing Zuo; Lijun Liu; Xueyang Tang; Lei Yang (PLoS ONE, 2026)
Objectives This study aimed to evaluate the 7-year outcomes of proximal humeral chondroblastoma treated with intralesional curettage, electrocauterization of the cavity and bone grafting in pediatric patients. Methods A total of 17 patients diagnosed with proximal humeral chondroblastoma who underwent surgical treatment consisting of intralesional curettage, cavity electrocauterization, and bone grafting at our center between January 1, 2008, and January 1, 2018, were retrospectively enrolled. All patients received postoperative splint immobilization for four weeks and were followed up for a minimum of seven years. Tumor recurrence was evaluated based on clinical manifestations and radiographic X-ray examination. Clinical outcomes included functional performance assessed using the Musculoskeletal Tumor Society (MSTS) score and the Quick Disabilities of the Arm, Shoulder and Hand (Quick DASH) scale, as well as postoperative complications. Results In total, 17 patients with proximal humeral chondroblastoma were enrolled in our study, including 10 males and 7 females, with a mean age of 10.9 ± 1.8 years old (range from 8 to 14 years). Among these 17 cases, there were 6 cases with lesions extending through the epiphyseal plate, and 11 cases with lesions located inside the epiphysis. During follow-up, 1 patient suffered reoperation due to tumor recurrence. Shortening of the affected upper limb occurred in 9 patients (52.9%), which was significantly associated with a young age(P = 0.012). The mean shortening was 1.2 ± 0.9 cm compared with the contralateral limb. The overall mean postoperative MSTS was 27.5 ± 1.4 points, with no significant difference between observed the limb shortening group (27.3 ± 1.4) and the non-shortening group (27.8 ± 1.4,P = 0.550). The overall Quick DASH score averaged 4.8 ± 3.9 (0–15.9), and no statistically significant difference was detected between the shortening group (5.3 ± 4.5) and the non-shortening group (4.3 ± 2.8; P = 0.452). Conclusions Intralesional curettage, cavity electrocauterization and bone grafting is an optional treatment for children with proximal humeral chondroblastoma but still has a risk of recurrence. Shortening of the affected upper limb is a common complication, which is possibly associated with young age but has no impact on the final functional outcomes. Level of Evidence Level IV, retrospective case series.